Characteristics of Age and Oral Hygiene Status on Palatine Tonsil Size in Chronic Tonsillitis Patients - Tias Ayu Karina; Winny Yohana; Moch. Rodian (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
Introduction: Tonsillitis is an inflammation of the palatine tonsils that caused by the invasion of microorganisms into the mucous membranes of the tonsils. Age is related to the tonsils immunological activity on the size of the palatine tonsils. Oral hygiene is one of determinant risk factor for chronic tonsillitis. This study aims to provide a characteristics of age and oral hygiene in determining the size of the palatine tonsils in chronic tonsillitis patients. Methods: This systematic literature review was conducted online from January to March 2021 against articles reporting on age, palatine tonsils size, and oral hygiene on chronic tonsillitis. The search for articles referred to Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) which conducted through PubMed, PMC, Science Direct, and Google Scholar with the with the publication year 2015-2020. Selected articles met the criteria according to the PICO framework (Population, Intervention, Comparison, Outcome). The articles were screened by checking for duplication, reading the titles and abstracts, and the full text articles. Results: Twelve in 16 research articles (75%) mentioned that there was a relation between age and enlargement of the size of the palatine tonsils in chronic tonsillitis patients, and one in 16 articles (6,25%) mentioned that there was no relation between age and tonsillar hypertrophy. Three articles (18,75%) mentioned the role and relationship of bacteria in the oral cavity related to the process of the occurrence of chronic tonsillitis. Two in 3 research articles (67%) mentioned that there was a relation between the oral hygiene status and enlargement of the size of the palatine tonsils in chronic tonsillitis patients. One in 3 articles (33%) mentioned that there was no relation. Conclusion: Ages 5-15 years had T3 tonsil size (70%), ages 13-15 years had T2 tonsil size (80%), ages 16-48 years had T2 tonsil size (76.30%) and ages 19-25 years had T3 tonsil size (53%). This means that all ages could be experience of tonsil enlargement in chronic tonsillitis. Adults had bad oral hygiene status (76.30%), meanwhile in children only 14.47% in chronic tonsillitis patients.